A topic modelling approach for reviewing research on motor behaviour - Ong, Angelyn Hui Sze (2018)
Topic modelling is a statistical method which aims to discover the latent structure in large text corpora (Bagheri, Saraee, & De Jong, 2014) and allows researchers to make better informed decisions about the worthiness and timeliness of undertaking further research. However, hardly any topic modelling has been done for motor behaviour research, which is progressively expanding in volume (Schmidt, Lee, Winstein, Wulf & Zelaznik, 2018). This study sought to establish a bird’s eye view of the topics in motor behaviour research from the past 10 years. It also assessed the relevance of the NTU SSM syllabus by comparing it to the topics found. English Bibliographical records that fit the criteria were downloaded from the Web of Science and analysed in R with R Studio, via the topic modelling approach. 407 terms and 109 collective themes were suggested based on the generated terms. 12 topics had notable links to the SSM syllabus. The suggested terms were further classified into 7 suitable categories. Topic modelling revealed that emphasis of research is placed on neuroscience; how the brain controls movement and conditions that affect the brain. Contrastingly, the SSM syllabus focuses on the application of paradigms and theories to facilitate motor learning and development of motor skills. This study provides a macroscopic view on motor behaviour research from the past decade. Researchers can also easily focus on a specific aspect of this field via the 7 categories, while reviewers of the SSM syllabus can take these topics into account when updating the syllabus.